2007
DOI: 10.3402/ijch.v66i1.18221
|View full text |Cite
|
Sign up to set email alerts
|

Sharing results from complex disease genetics studies: a community based participatory research approach

Abstract: Objectives. Dissemination of research results to communities builds capacity of the community to understand and utilize the results. The objective of this manuscript was to propose a culturally appropriate approach to disseminate complex disease genetics research findings in small Alaska Native communities. Study Design. The Center for Alaska Native Health Research is a community-based participatory research project (CBPR) directed at understanding the interactions between genetic, nutritional and psychosocial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 19 publications
3
54
0
1
Order By: Relevance
“…The results of the present study are consistent with perceptions that genetic research is viewed as a 'double-edged sword' [22], research must address health priorities and have appropriate tribal oversight to be supported [25], researchers must be trustworthy partners throughout the research process, and that CBPR is a model for that engagement [33]. Participants' desire to know the history of previous pharmacogenetic research done at the organization and with the partners is consistent with the notion that long-term partnerships on community priorities were an important consideration of participants [23].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of the present study are consistent with perceptions that genetic research is viewed as a 'double-edged sword' [22], research must address health priorities and have appropriate tribal oversight to be supported [25], researchers must be trustworthy partners throughout the research process, and that CBPR is a model for that engagement [33]. Participants' desire to know the history of previous pharmacogenetic research done at the organization and with the partners is consistent with the notion that long-term partnerships on community priorities were an important consideration of participants [23].…”
Section: Discussionsupporting
confidence: 82%
“…Shaw et al found that AN people viewed pharmacogenetic research as carrying both risks (e.g., healthcare rationing, misuse of information and stigma to individuals and the AN community) and rewards (e.g., decreased healthcare costs, improved clinical outcomes). A communitybased participatory research (CBPR) approach has been shown to be a successful method in bridging the gap between science and practice through community engagement, particularly in AI/AN populations [32][33][34].…”
mentioning
confidence: 99%
“…CBPR fosters open communication, trust, accountability, and keeps participants engaged from conceptualization to implementation of the project (Ammerman, Corbie-Smith, St. George, Washington, Weathers, & Jackson-Christian, 2003; Boyer, Mohatt, Pasker, Drew, & McGlone, 2007; Pazoki, Nabipour, Seyednezami, & Imami, 2007). Community ownership of the project, along with the relevancy of the information generated for the promotion and implementation of intervention strategies, is fundamental to the success and sustainability of the project.…”
mentioning
confidence: 99%
“…Because incorporating biological sampling into a CBPR framework is new in Greenland, it will become important for the members of the research team involved in the Greenland Sexual Health Study to communicate to the communities the status of the bio-banking process. This must be done in order to strengthen the relationship between the researchers and the communities, and to build trust and understanding of a research process that involves collecting biological samples (12).…”
Section: Challenges Of Using Cbpr In Greenlandmentioning
confidence: 99%